The Intersection of Diabetes and Cardiovascular Disease—A Focus on New Therapies - Dhindsa, Devinder S.; Sandesara, Pratik B.; Shapiro, Michael D. (Frontiers in Cardiovascular Medicine, 2018)
Diabetes is a leading cause of cardiovascular disease and its associated morbidity. While the medical community has had access to numerous glucose lowering therapies over the last decades, it was not until recently that newer agents demonstrated improvement in cardiovascular outcomes. In particular, diabetes care and management of its attendant cardiovascular risk is now being revolutionized with the development and provision of the SGLT-2 inhibitors and GLP1- receptor agonists. Given the exciting data with these new classes of diabetes therapeutics, there is a clear need to improve education and utilization of these evidence-based medications across a wide spectrum of clinicians, including cardiologists. The aim of this review is to familiarize the cardiovascular specialist with the benefits and harms of the most commonly used oral anti-hyperglycemic medications, with an emphasis on SGLT-2 inhibitors and GLP-1 receptor agonists.